Pemanfaatan E-learning dan Kecerdasan Buatan untuk Meningkatkan Kualitas Materi dan Evaluasi Pembelajaran pada Pendidikan Dasar - Bambang Soelistijanto; Agung Hadhiatma; Agung Hernawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
E-learning has been proven to significantly improve the quality of learning. This ICT-based learning allows the teaching and learning process to take place anywhere and anytime (ubiquitous learning). Furthermore, artificial intelligence (AI) can be applied to improve the quality of teaching materials and evaluation process. In this community service program (PkM), we implemented AI-assisted e-learning in the teaching and learning process at Sawah Elementary School, Panggang, Gunung Kidul. To this end, we first built the ICT infrastructure to support e-learning. A computer server was installed using Moodle as the learning management system (LMS). Following this, a series of training sessions were held, including Moodle administrator training for one teacher, digital classroom management and Moodle question creation training for all teachers, and Moodle training for students, which included online quizzes. At the end of the PkM, we conducted an evaluation with the teachers and students to measure their abilities and responses after all the training. Although teachers and students’ abilities on average showed average results in Moodle and AI mastery, their satisfaction with the training was very high, and they expected that this training could continue in the coming years.